Penerapan Berbagai Pola Agroforestri Hutan Rakyat Di Kabupaten Lumajang Dan Potensi Pendapatannya - Iryeni Andi Pratiwi; Aryo Fajar Sunartomo; Luh Putu Suciati (UPT Penerbitan Universitas Jember, 2018)
People's forest is a forest that is built, managed, and used by people with an area of at least 0.25 hectares of overgrown plants with timber or other kinds of plants on the land belonged. The importance of forest peoples as the provider of the wood. Government program encouraging the agroforestri so that the community grow timber and meets the needs of timber in the country. But farmers are reluctant to grow timber because of the length of time waiting for the harvest. The pattern of agroforestri that gives a high income will provide incentives for farmers to grow timber. This research aims to know (1) the description of the various patterns of agroforestri in Lumajang (2) potential income of agroforestri pattern in Lumajang. Research methods used in this research is descriptive and analytic methods. Sampling method is the Proportionate Random Sampling. Data collection methods the method of observation, interview with kuisio